O futuro do passado: uma cidade para o progresso e, o progresso para cidade em João Durval Carneiro. (1967-1971) - Corrêa, Diego Carvalho (2012)
This work investigated the process of urban modernization undertaken by João Durval Carneiro’s government (1967-1971) in Feira de Santana. Its main question were how did Durval become representative and driver of such modernization project – which is characterized as a formulation of hegemony – and, therefore, a politician in act (Gramsci). We analyze the context that precedes Durval government, the “bionic” administration of Joselito Amorim (1964-1965), which is important for understanding the transition time and the efforts for realization of modernization under the influence of local Economic Action Plan. We studied political alliances among both civil society groups such as industrialist and businessmen, and political society agents, including groups outside the city, local class fractions synchronized with national and Bahia’s context, which allowed the uprising of those particular model of modernization in Feira de Santana. We analyze also the UDN and ARENA parties in Feira de Santana, paying attention to its characteristic of organizers of a speech of progress and modernization in the city between 1954 to 1971, speech that has become stronger when turned into modernization project assumed by João Durval Carneiro’s government. This mayor became representative and spokesperson for those project of political domination, intellectual and moral direction of the local society, so his party was seen as a kind of modern prince in Feira de Santana.